The Microevolution of Routines: How Problem Solving and Social Preferences Interact - Loch, Christoph H.; Sengupta, Kishore; Ahmad, M. Ghufran (Organization Science, 2013)
Routines are repetitive patterns of activity within a group, action patterns that help the group to solve problems and organize its way of functioning. Routines address issues of problem solving as well as issues of internal integration, such as regulating group identity, status distribution, and relationships. This study uses an experiment with three-person groups to examine how routines evolve in the interaction of problem-solving and internal integration dynamics. In line with previous work, we find that groups do indeed develop problem-solving routines over time and use them consistently. Furthermore, group members internalize and retain routines in their individual decisions. The formation and retention of these routines is, however, affected by social comparisons. Groups that have a strong sense of group identity use their problem-solving routines more consistently. Their members also better retain the routines in their individual decisions. In contrast, we find that differentiated status within a group distorts its problem-solving routines by overweighting the influence of the high-status member. Status also interferes with the formation and retention of routines, in that groups are relatively less consistent in using them and their members show lower retention of the routine in their individual decisions. Finally, a strong relationship between two of the three members in a group (leaving the third group member out) enables the two to engage in consistent problem solving, but concomitantly, the group as a whole is less able to apply its routines consistently, and group retention of routines also suffers.